Seawater quality criteria derivation and ecological risk assessment for oil pollution in China. (May 2019) - Yan, Zhenguang; Pan, Jinfen; Gao, Fu; An, Zhe; Liu, Huifang; Huang, Yi; Wang, Xiaobing
Abstract: The establishment of water quality criteria (WQC) for oil pollutants is the basis for ecological risk assessment of marine oil pollution. Ecotoxicity data of oil pollutants to marine organisms in China were collected and toxicity test of oil to nine Chinese marine organisms were performed. Based on the WQC guidelines of the United States, the sea WQC of oil pollutants in China were studied. Then, the ecological risk of oil in 7 sea areas of China was assessed. Results showed that the long-term and short-term criteria of oil pollutants in China are 7.3 μg/L and 36 μg/L, respectively. Except for Qinhuangdao and Xiamen sea areas, the highest oil concentration in the other five sea areas exceeded the long-term WQC by >10 times, and the highest oil concentration in the Pearl River Estuary exceeded the long-term WQC by >100 times, indicating serious ecological risk. Highlights: The short-term criteria of oil pollutants in Chinese sea areas are 36 μg/L. The long-term criteria of oil pollutants in Chinese sea areas are 7.3 μg/L. High sensitivity of the Cancer larvae results in the conservative oil criteria. The oil pollution posed serious ecological risk in the Pearl River Estuary.